2017
DOI: 10.2174/1573406413666170421102353
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of DIDS-Induced Inhibition of Voltage-Dependent Anion Channels (VDAC) on Cellular Response of Lymphoblastoid Cells to Ionizing Radiation

Abstract: Our results suggest that VDAC control cellular response to ionizing radiation through modulation of the ROS- and NO-dependent signaling pathways. Inhibition of VDAC with DIDS induced apoptosis in irradiated K562 lymphoblastoid cells points at DIDS, as a promising agent to enhance the effectiveness of radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…) and voltage‐dependent anion channel in mitochondria (Skonieczna et al . ). The K + channel agonists ML277 and NS1643 are not very widely used and therefore data on their specificity are scarce.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) and voltage‐dependent anion channel in mitochondria (Skonieczna et al . ). The K + channel agonists ML277 and NS1643 are not very widely used and therefore data on their specificity are scarce.…”
Section: Discussionmentioning
confidence: 97%
“…DIDS, for example, is not especially selective for CaCCs. DIDS is a widely used inhibitor of cellular anion conductances and was demonstrated to suppress various Cl − channels (Duan & Nattel, 1994), the Cl − /HCO 3 − exchanger (Helbig et al 1988) and voltage-dependent anion channel in mitochondria (Skonieczna et al 2017). The K + channel agonists ML277 and NS1643 are not very widely used and therefore data on their specificity are scarce.…”
Section: Figure 9 K + Channel Agonists Have No Effect On Cat Alternamentioning
confidence: 99%
“…VDACs are transmembrane channels that transport ions and metabolites and play an important regulatory role in ferroptosis 15 . Yagoda et al 4 found that erastin acts on VDACs, leading to mitochondrial dysfunction and resulting in a large amount of released oxides, eventually leading to iron-mediated cell death.…”
Section: Ferroptosis Mediated By Mitochondrial Vdacsmentioning
confidence: 99%
“…Overall ROS levels were measured by flow cytometry using specific dyes, 2′,7′-dichlorofluorescin diacetate (DCFH-DA; Sigma) for reactive oxygen species (ROS), CellROX Green (Life Technologies) for superoxide anion (•O 2 -), or MitoSOX™ Red (Life Technologies) for mitochondrial superoxide and DAF-FM (Life Technologies) for nitric oxide (NO), as described previously [13, 14]. DCFH-DA, a cell-permeable non-fluorescent probe, converts into the highly fluorescent 2′,7′-dichlorofluorescein (DCF) upon deacetylation by intracellular esterases and oxidation by ROS.…”
Section: Methodsmentioning
confidence: 99%